2007
DOI: 10.1007/s00220-007-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Complex/Symplectic Mirrors

Abstract: We construct a class of symplectic non-Kähler and complex non-Kähler string theory vacua, extending and providing evidence for an earlier suggestion by Polchinski and Strominger. The class admits a mirror pairing by construction. Comparing hints from a variety of sources, including ten-dimensional supergravity and KK reduction on SU(3)-structure manifolds, suggests a picture in which string theory extends Reid's fantasy to connect classes of both complex non-Kähler and symplectic non-Kähler manifolds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It then follows that the set of forms {α tor β } and {ω tor,α } constructed in this way satisfy relations equivalent to (C.7) and (C.8), namely [54] More importantly, this means that the phases (C.2) that these forms associate to each torsional 2 and 3-cycle of our construction are exactly the same as the bump forms δ α 4 and δ 3,β and, in this sense, they can be thought as the same elements of Tor H 4 (M 6 , Z) and Tor H 3 (M 6 , Z).…”
Section: D-branes and Torsion Invariantsmentioning
confidence: 95%
See 2 more Smart Citations
“…It then follows that the set of forms {α tor β } and {ω tor,α } constructed in this way satisfy relations equivalent to (C.7) and (C.8), namely [54] More importantly, this means that the phases (C.2) that these forms associate to each torsional 2 and 3-cycle of our construction are exactly the same as the bump forms δ α 4 and δ 3,β and, in this sense, they can be thought as the same elements of Tor H 4 (M 6 , Z) and Tor H 3 (M 6 , Z).…”
Section: D-branes and Torsion Invariantsmentioning
confidence: 95%
“…Constructing such torsional analogues of harmonic forms is quite similar to finding an appropriate basis of p-forms to perform dimensional reduction on SU(3)-structure manifolds [54,[60][61][62], since both problems deal with p-forms that are invisible to de Rham cohomology and correspond to the internal profile of massive 4d modes. with ω tor r−1 a globally well-defined (r − 1)-form, and k ∈ Z such that kα tor r is trivial also in Tor H r (M D , Z).…”
Section: Massive Rr U(1)'s From Torsionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different context, it was also shown that IIA vacua should always be symplectic, whereas IIB vacua should be complex [92]. Mirror symmetry between complex and symplectic manifolds has been discussed in [98].…”
Section: Discussionmentioning
confidence: 99%
“…This is the underlying idea of compactifications on SU (3)×SU (3) structure manifolds. Such compactifications have been extensively studied in [6,8,7,[9][10][11][12][13][14][15][16][17][18]. Interestingly, the latter show a natural connection to Hitchin's generalized geometry [19,20], where in this picture SU (3)×SU (3) appears as the structure group of the generalized tangent bundle T M 6 ⊕ T * M 6 of the internal manifold M 6 .…”
Section: Introductionmentioning
confidence: 99%